Spaces of female subordination in the Brazilian adaptation The Tempest by William Shakespeare (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This essay aims to analyze the play O Toró, an adaptation of The Tempest, by William Shakespeare. The play, premiered in October 2023, brings new features to the Shakespearean plot, starting with the replacement of two male characters with their female counterparts. Not only that, the use of elements from Afro-Brazilian religions in the narrative adds new layers of meaning to the hierarchy of relationships established by the characters. In our analysis we focus on a feminist-decolonial approach to how the uncritical addition of these elements reiterates the hegemony of sexist and colonial discourses regarding expectations of the place women should occupy according to patriarchal discourse.
Keywords: The Tempest; decoloniality; feminism; William Shakespeare